Proportion of Diabetes Mellitus in Koja Hospital - Ndraha, Suzanna; Dwicahya Putra, Hervico; Dwicahya Putra, Hervico; Derza Polas, Caesaredo; Derza Polas, Caesaredo; Laura Sabrina, Ratih; Laura Sabrina, Ratih; Huda, Khairul; Huda, Khairul (Lembaga Penelitian Universitas YARSI, 2019)
Diabetes mellitus (DM) is one of the most common disease found in clinical practice in Koja General Hospital. According to the previous research, the prevalence of diabetes patients has never been investigated. Aim of this study was to find out the proportion of diabetes subjects hospitalized in Koja General Hospital.This was a descriptive study with a cross sectional approach. Data was taken by consecutive sampling method from diabetes mellitus subjects aged ≥18 years who were hospitalized in the department of internal medicine Koja General Hospital in the period of August 20, until September 30, 2018.The proportion of diabetes subjects in Koja General Hospital was 42% (155 patients) out of a total of 368 subjects. The age of diabetes subjects with the majority of elderly adults (26-65 years) as much as 84% (131 patients) of 155 diabetes subjects. Gender were dominated by woman as 59% (91 patients) out of a total of 155 subjects and the remaining men were 41% (64 patients). The most frequent indication of treatment in diabetes subjects is chronic kidney failure (CKD) as much as 22 patients (14.2%).The proportion of diabetes subjects who were hospitalized was 42% (155 people) of a total of 368 subjects.